A study on the effectiveness of Point of Purchase (PoP) display at the Children's Department, Jaya Jusco Bandar Baru Klang / Azrina Ashahar - Ashahar, Azrina (1997)
Point of purchase (POP) displays must done a specific job - attract the attention of the customer in the store. If it does not do that, it has failed to do the job. POP is a form of sales promotion advertised for a merchandise. POP can help the sales person and promote the company's image. For example, if the wrong description is given and the POP is untidy, it will give the customer an impression that the goods are not worth the price and the company's image will be affected.